Development and Validation of RP-HPLC Method for Quantification of Fluconazole in Pharmaceutical Formulations - Felimban, Alaa Mohammed Jamil; Abou El Ela, Amal El Sayeh Fadl; Aleanizy, Fadilah Sfouq; Taha, Ehab (Journal of medical and pharmaceutical sciences, 2020)
A rapid and simple reversed phase high performance liquid chromatography method to quantify fluconazole which is a triazole antifungal drug that is available in pharmaceutical oral dosage forms (tablets and suspension) and parenteral intravenous injection. It is used mainly against Candida albicans. The chromatography was carried out using Nova-Pak C18 (3.9 x 150 mm) Column at 260 nm wave length using a photodiode array detector at room temperature. The mobile phase consisted of 0.01 M phosphate buffer of pH 7 and acetonitrile in a ratio of 75:25 v/v delivered at a flow rate of 1 ml/min. The retention time was 2 min with a short run time of 2.5 min. The method was validated with respect to linearity, precision, accuracy, and specificity. The linearity was established over the concentration range between 1-200 μg/ml. The percentage of drug recovered after analysis for Intra-day was between 92.64% and 108.00% while the inter-day was between 93.17% and 100.25%. The proposed method is easy to apply, it is a fast method with a retention time of only two minutes making it perfect for determining routine analysis with low fluconazole sample concentrations and it is the quickest method ever recorded for fluconazole analysis by HPLC.